Implementation of property‐level flood risk adaptation (PLFRA) measures: Choices and decisions. (5th December 2019) - Attems, Marie‐Sophie; Thaler, Thomas; Genovese, Elisabetta; Fuchs, Sven
Abstract: Hydrometeorological events are highly costly and have strong impacts on the human‐environment system. Effective response requires effective risk management concepts and strategies at individual and watershed level to increase community resilience. Focusing on flood risk and the information associated with it, individual risk behavior in the shape of implementing property‐level flood risk adaptation (PLFRA) measures is often overlooked. For this research, a comprehensive overview of possible PLFRA measures for homeowners in flood risk areas was made, as well as the possible costs and technical feasibility for new and existing buildings. To complement this, insights into risk mitigation behavior are essential due to the ongoing shift to risk‐based and individualized flood risk management, which require a contribution from flood‐prone households to risk reduction. Results show that PLFRA measures differentiate in their effectiveness, cost‐efficiency and technical feasibility, and full protection can never be guaranteed. Considering risk mitigation behavior, literature generally distinguishes between situational factors (such as communication and economic subsidies) and personal factors (such as personal and psychological components influencing individual behavior). This article is categorized under: Engineering Water > Planning Water Science of Water > Water Extremes Abstract : As there are several options to adapt a private house to flood hazards, a homeowner is confronted with several decisions concerning the costs, practicability, and implementation process of such. The images demonstrate a few examples of PLFRA measures such as elevation, dry flood‐proofing, and adapting the building shape.